Gender inequality in terms of wages in Kazakhstan - Suleimenova, Anel; Kašparová, Eva, 1958-; Černá, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
This bachelor thesis analyzes the problem of gender inequality in terms of wages in Kazakhstan. The thesis aims to study the problem of gender inequality and to reveal it on the example of wages of company X's employees. The theoretical basis of the thesis focused on reasons for the existence of gender inequality from sociological and economic points of view, gender policy and history of the formation of gender inequality in Kazakhstan, as well as on differences in female and male wages in Kazakhstan. The author used quantitative method for the research in the practical part. The research investigates the relationship between gender and wage in company X. In order to support data protection rules and desire of the company X to maintain privacy, the name of the organization was not revealed in the current thesis. Results showed the persistent existence of the gender pay inequalities in company X from 2015 to 2018. The findings of the current research serve to provide recommendations for the reduction of gender inequalities in terms of wages in company X.
Vedoucí práce: Eva Kašparová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses